2008
DOI: 10.1103/physreve.78.050903
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations and patterns in interacting populations of two species

Abstract: Interacting populations often create complicated spatiotemporal behavior, and understanding it is a basic problem in the dynamics of spatial systems. We study the two-species case by simulations of a host-parasitoid model. In the case of coexistence, there are spatial patterns leading to noise-sustained oscillations. We introduce a measure for the patterns, and explain the oscillations as a consequence of a time-scale separation and noise. They are linked together with the patterns by letting the spreading rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
103
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(113 citation statements)
references
References 33 publications
10
103
0
Order By: Relevance
“…This is the reason why the corresponding games exhibit similar behaviors resembling those observed for the rockpaper-scissors games on square lattice at different evolutionary rules. Due to the "cyclic" symmetries for all the three basis games the four strategies are present with the same frequency [35][36][37][38][39]. The strategy frequencies can be tuned by varying the strength of these components [40][41][42].…”
Section: Cyclic Gamesmentioning
confidence: 99%
“…This is the reason why the corresponding games exhibit similar behaviors resembling those observed for the rockpaper-scissors games on square lattice at different evolutionary rules. Due to the "cyclic" symmetries for all the three basis games the four strategies are present with the same frequency [35][36][37][38][39]. The strategy frequencies can be tuned by varying the strength of these components [40][41][42].…”
Section: Cyclic Gamesmentioning
confidence: 99%
“…In recent years, many models for the RPS cyclic competition have been considered. In particular, various two-dimensional versions of the model introduced by May and Leonard [22] have been studied [15,[17][18][19]21,23]. In spatial variants of the May-Leonard model, it was found that mobility implemented by pair-exchange among neighbors can significantly influence species diversity: Below a certain mobility threshold species coexist over long periods of time and selforganize by forming fascinating spiraling patterns, whereas biodiversity is lost when that threshold is exceeded [15].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21]. In recent years, many models for the RPS cyclic competition have been considered.…”
Section: Introductionmentioning
confidence: 99%
“…In experiments with Escherichia coli, for example, it has been shown that arranging the bacteria on a Petri dish is crucial for keeping all three competing strains alive [8,36]. Accordingly, simulations of spatial rock-paper-scissors and related games of cyclic dominance have a long and fruitful history [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56], which is firmly rooted in methods of statistical physics. In general, if the mobility in the population is sufficiently small [7], the spatial rock-paper-scissors game leads to the stable coexistence of all three competing strategies, whereby the coexistence is maintained by the spontaneous formation of complex spatial patterns.…”
Section: Introductionmentioning
confidence: 99%